The Perfection of God's Creation in the Balance of Nature: The Relevance of QS. Ar-Rahman: 7-9 from the Perspective of the Qur'an and Modern Science - Dinda Kartika; Faisal Abdullah (Journal of Science and Research, 2025)
The work of Allah SWT is reflected in the perfection of His balanced creation, as depicted in Surah Ar-Rahman, verses 7-9, which emphasize the harmony of heaven and earth, and the balance of the universe. This paper analyzes the relevance of these verses from the perspective of the Qur'an and modern science, with the aim of uncovering the synergy between divine revelation and contemporary empirical discoveries. The approach used is thematic interpretation (tafsir mawdu'i) based on the Qur'an, combined with interdisciplinary scientific studies such as physics, cosmology, ecology, and the laws of thermodynamics. The analysis shows that the Qur'anic description of "the heavens raised high without pillars" (verse 7) aligns with the concept of the expansion of the universe (the Big Bang theory), while "the balance of the earth" (verses 8-9) reflects the principle of ecosystem homeostasis and the law of conservation of energy in science. This perspective not only strengthens Muslims' belief in the scientific miracles of the Qur'an but also opens a constructive dialogue between religion and science to address the global environmental crisis. In conclusion, the perfection of Allah's creation demands that humans maintain the balance of nature as a divine mandate.